Gender and Class Type Disparities in Higher Education Students’ Resilience - Maria Oktasari; Siti Aminah; Herul Wahyudin (Proceedings Series of Educational Studies, 2023)
The ability to adapt to difficult situations or pressure is important for students. This study examines the intersection of gender and class type in shaping the resilience of higher education students. This comparative research was conducted on 228 students of average age. Data were collected using a brief resilience scale. Data analysis used an independent t-test with the help of JASP. The analysis results show that: 1) there is a significant difference between the resilience of male and female students. 2) No significant difference exists in the resilience of regular and employee-class students. The research contributes to the greater discussion on equality in higher education, providing insights for institutions to establish an environment and provide counseling services where all students can prosper despite the challenges they experience.